Digital Technology in Capacity Development Enabling Learning and Supporting Change - Wild, Joanna; Nzegwu, Femi (African Minds, 2023)
This book focuses on digital approaches to capacity development, reflecting the greater interest in how digital tools and platforms can be used for capacity development in the 'Global South'. While Covid-19 demonstrated some of the benefits of online learning, the widespread, often uncritical adoption of online tools driven by necessity has left many with an experience of 'emergency online learning'. This book aims to assist in the design of technology-enhanced capacity development by sharing evidence of practices that are principled rather than rushed; inclusive rather than creating new digital divides. We have worked to evidence how technology can be leveraged effectively to enhance or strengthen capacities of individuals, teams or systems. We make clear that there are no magic bullets, that online approaches are not simply quicker or cheaper substitutes, and that solutions need to be selected carefully, designed well, and significant time invested if it is to work well. We hope Digital Technology in Capacity Development will be of interest to researchers and practitioners in a range of institutions, whether they are directly responsible for designing, delivering or evaluating new initiatives or whether they are advising or funding those who do.